Malacca and beyond ... : to catch me a star - Harrison, Bernard, 1951-; Lai, Jerry (Singapore : Media Masters, 2002)
'In Catch Me A Star, author stirs up gentle memories, combines them with cameos of life in rural Malaysia and offers intriguing alternative images of the path to which we so often feel shackled in our unpredictable and fruquently arduous journey through life. A timeless tale for children and adults alike.'
Keywords: English fiction -- Malaysian authors; Short stories, English; Fairy tales